2003
DOI: 10.1097/00000658-200301000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Have Outcomes of Incisional Hernia Repair Improved With Time?

Abstract: Incisional hernia repair is associated with high cumulative rates of reoperative repairs. The expectation that important measures of adverse outcome have improved in recent eras is not supported by the results of this large population-based study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
267
2
12

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 494 publications
(286 citation statements)
references
References 12 publications
5
267
2
12
Order By: Relevance
“…The use of mesh implants in hernia surgery has become increasingly widespread, due to good postoperative results and low rates of long-term recurrence [5,18]. Polypropylene has been established as the basic synthetic material for mesh; it is a versatile thermoplastic polymer that exhibits excellent chemical resistance, low density, high tensile strength and a relatively high melting point, especially in comparison to its counterpart, polyethylene.…”
Section: Discussionmentioning
confidence: 99%
“…The use of mesh implants in hernia surgery has become increasingly widespread, due to good postoperative results and low rates of long-term recurrence [5,18]. Polypropylene has been established as the basic synthetic material for mesh; it is a versatile thermoplastic polymer that exhibits excellent chemical resistance, low density, high tensile strength and a relatively high melting point, especially in comparison to its counterpart, polyethylene.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year rate of reoperation was 24% after the first reoperation, 35% after the second, and 39% after the third, and the 7-year rate after three reoperations approached 50%. 16 This data underscores the importance of minimizing the risk for subsequent reoperations by employing the best evidencebased approach to the first hernia repair.…”
Section: Introductionmentioning
confidence: 91%
“…15 This fact is illustrated by the results of a retrospective cohort study of a population-based hospital discharge database which showed that 12% of patients undergoing incisional hernia repair required at least one subsequent reoperation within 5 years. 16 In addition, the length of time between reoperations progressively shortens after each additional Keywords ► components separation ► biologic mesh ► ventral hernia…”
Section: Evolution Of Prosthetic Implantsmentioning
confidence: 99%
“…In 1997, in Germany, 85% of incisional hernias repairs was still performed without prosthetic mesh, 26 while in 1999, in Washington state, 35% of incisional hernias was repaired without mesh. 27 In the Netherlands in 2002, surgeons failed to use a mesh in 40% of incisional hernia repairs. 8 To determine what type of hernia repair should be performed, long-term results of incisional hernia repair are needed.…”
mentioning
confidence: 99%